Analysis Need Education for Postpartum Mothers - Runiari, Nengah; Ruspawan, Dewa Made; Suratiah, Suratiah (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: Postpartum mothers need education to maintain themselves and their babies. Only a little study about material education is based on what a mother and husband need. The study aims to explore the need for education for postpartum mothers and identify materials, methods, and educational media needed by postpartum mothers.   Methods: This study employed mixed methods with a sequential exploratory design. Stage 1 was done through a qualitative study with in-depth interviews with the seven participants using purposive sampling. Analyze the data with thematic deductive analysis. The quantitative phase used 300 postpartum mothers with a purposive sampling technique. An instrument study questionnaire was prepared by researchers, and a trial was conducted on 50 respondents with valid and reliable results. Quantitative data analysis with descriptive analysis   Results: It found six themes, namely "education to take care of a mother,” “education needs to take care of a baby,” "time-giving information,” "methods of providing education,” educational media,” and "sources of information.” The most needed maternal care educational material is about breastfeeding (4.55 ± 0.531), breast care (4.46 ± 0.531), and mental health (4.45 ± 0.584). Material related to baby care that is mainly needed is immunizations (4.59 ± 0.493), signs and dangers of newborns (4.55 ± 0.685), and umbilical cord care (4.53 ± 0.557). The media chosen by the mother are online media and video. Direct education method by health workers. Timing of education during pregnancy.   Conclusion: Giving education should be customized with materials needed by the mother. Education will succeed if supported by educational media, appropriate methods, and time in education and carried out by healthcare professionals.